Weight Category-dependent Trunk Muscle Strength and its Relation with LBP in Elite Judokas - Okada, Takashi (Sports Med Int Open, 2020)
Trunk muscle strength (TMS), especially rotator, is an important factor for both athletic performance and injury risks in judokas. However, the characteristics of TMS that depend on weight categories are still unclear. Although inadequate TMS might cause low back pain (LBP), the relationship between these two variables is not fully understood. In this study, weight category-dependent TMS and its relationship with LBP was investigated in Japanese judokas. The subjects were 66 male collegiate judokas, who were classified into the lightweight (N=14), middleweight (N=29) or heavyweight (N=23) category. The peak torques of extensor, flexor and rotator muscles were measured. The LBP group and non-LBP group were defined by questionnaire. TMS (normalized by body weight) in the heavier weight category showed a lower tendency in comparison with other categories, except for rotator strength. Significant differences were observed in the extensors (90 and 120 °/s; P<0.05) and flexors (60, 90 and 120 °/s; P<0.05). The LBP group (N=9) only showed significantly lower extensor (60 °/s; P<0.05) and right-rotator (60 °/s; P<0.01) strength in the heavyweight category compared with the non-LBP group (N=14). The relative TMS of judokas decreased in the heavyweight category, except for trunk rotator strength. Notably, low trunk extensor and rotator strengths are risk factors for LBP in heavyweight judokas.